The Effect of Personality, Work Experience, and Job Characteristics on Employee Work Loyalty at CV Michael Hutama Persada - Reinaldo Geovanni Tanawan; Mukmin Suryatni (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study aims to examine the effect of personality, work experience, and job characteristics on employee work loyalty at CV Michael Hutama Persada. Work loyalty is an essential factor for organizational sustainability as it reflects employees’ commitment, dedication, and willingness to remain with the organization. This research employs a quantitative approach with associative and causal research designs. The research population consists of all 50 permanent employees of CV Michael Hutama Persada; therefore, a saturated sampling technique was applied. Data were collected through questionnaires using a five-point Likert scale and analyzed using SPSS software. The data analysis techniques included validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that personality has a significant effect on work loyalty with a negative relationship. Work experience has a positive and significant effect on employee work loyalty, while job characteristics show a negative and significant effect on work loyalty. Simultaneously, personality, work experience, and job characteristics significantly influence employee work loyalty. These findings provide managerial implications for organizations in developing effective human resource management strategies to enhance employee loyalty and long-term organizational performance.